2013
DOI: 10.1186/1423-0127-20-92
|View full text |Cite
|
Sign up to set email alerts
|

DNA transposon-based gene vehicles - scenes from an evolutionary drive

Abstract: DNA transposons are primitive genetic elements which have colonized living organisms from plants to bacteria and mammals. Through evolution such parasitic elements have shaped their host genomes by replicating and relocating between chromosomal loci in processes catalyzed by the transposase proteins encoded by the elements themselves. DNA transposable elements are constantly adapting to life in the genome, and self-suppressive regulation as well as defensive host mechanisms may assist in buffering ‘cut-and-pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 232 publications
(269 reference statements)
2
54
0
1
Order By: Relevance
“…Presently researchers are concentrating more on developing cell penetrating peptides, nano shell, sleeping beauty transposon, conjugated polymers, and biological vectors to be effective in non-viral gene transfer as compare to viral vectors [33][34][35][36][37] Apart from above mentioned SPION (super paramagnetic nano particle), mitochondria targeting strategies {mitochondria leader peptide (MLP), mitochondria targeting sequence (MTS) +DNA, liposome based carrier (Dequalinium) DQAsomes} are also under present review of developing into potential gene transfer agent [38].…”
Section: Discussionmentioning
confidence: 99%
“…Presently researchers are concentrating more on developing cell penetrating peptides, nano shell, sleeping beauty transposon, conjugated polymers, and biological vectors to be effective in non-viral gene transfer as compare to viral vectors [33][34][35][36][37] Apart from above mentioned SPION (super paramagnetic nano particle), mitochondria targeting strategies {mitochondria leader peptide (MLP), mitochondria targeting sequence (MTS) +DNA, liposome based carrier (Dequalinium) DQAsomes} are also under present review of developing into potential gene transfer agent [38].…”
Section: Discussionmentioning
confidence: 99%
“…16 It would be interesting to determine whether our technology can be transferred to other widely established cell lines such as Chinese hamster ovary (CHO) or HEK293T, and to investigate the extent to which different host cell lines would be beneficial in terms of the library sizes that could be generated and screened, the ratio of membrane-bound vs. secreted IgG that could be achieved with these non-B cell lines, and finally how the properties of the isolated antibodies compare with antibodies isolated from the B cell host cell line employed here. Importantly, PiggyBac seems to be active in a wide range of mammalian cell lines, 45,52,53 and thus could in principle be applied to other cell systems of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these first studies also showed that transposition was totally blocked when the transposase was expressed at high levels. 50 It is still not clear whether this phenomenon, referred to as overproduction inhibition (described in 15 ), in the mouse reflects restricted transposon mobility or toxicity in transfected hepatocytes. In accordance, however, we found that the transposase expression level had to be carefully tuned by use of an appropriate promoter when transposon and transposase gene were delivered on a single plasmid, leading to correction of hemophilia B in a preclinical mouse model.…”
Section: Plasmid Dna As a Source Of Genome-modifying Enzymesmentioning
confidence: 99%